LINC-21. PROGNOSTIC FACTORS AND SURVIVAL OF LOW-GRADE GLIOMAS IN CHILDREN AND ADOLESCENTS – A MULTICENTER STUDY IN PERU. (3rd June 2022) - Diaz-Coronado, Rosdali; Hernández-Broncano, Eddy; Casavilca-Zambrano, Sandro; Campos-Sanchez, Danny; Maza, Ivan; Tello, Mariela; Leon, Esmeralda; Cañari, Hernan; Custodio, Javier; Ojeda-Medina, Luis; Negreiros, Tatiana; Cordova, Olga; et al.
Abstract: BACKGROUND: Low-grade gliomas (LGG) are the most common central nervous system (CNS) tumors in children. Peru is an index country for the Global Initiative for Childhood Cancer (GICC). As part of the Initiative, a multidisciplinary brain tumor team was formed in 2020 that includes five national reference centers: National Institute of Neoplastic Diseases, National Children's Health Institute-San Borja, National Children's Health Institute-Breña, Edgardo Rebagliati Martins National Hospital and Guillermo Almenara Irigoyen National Hospital. This multicenter study sought to evaluate the survival and prognostic factors of patients younger than 18 years diagnosed with LGG, an index cancer for the GICC. METHODS: A retrospective study included all patients diagnosed with LGG in the five centers between 2014 and 2018. We analyzed clinical characteristics, histology, and treatment modalities. We used the Kaplan-Meier method for survival. RESULTS: 194 patients were registered; 136 patients were included. M/F ratio was 1.2, mean age 7 years old. The most frequent location was infratentorial (42.2%), supratentorial (34.9%), optic/chiasm/sellar (11%) and brainstem (11.9%). The most frequent histological types were pilocytic astrocytoma (61%), diffuse astrocytoma (10.3%), oligodendroglioma (5.2%), and other low-grade neoplasms (23.5%). Surgery was performed in 109 patients (83.2%). Chemotherapy alone was used in 17 (12.5%), while radiotherapy in 20 (14.7%). Overall survival at 5 years was 82.9% (95% CI 73.3 - 89.4). Age younger than 3 years (p=0.002), diffuse histological type (p=0.04), and location in the brainstem (p=0.001) were factors associated with a worse prognosis. CONCLUSIONS: Within the framework of the GICC, this work is one of the first steps to understand the current context of pediatric CNS tumor care in Peru. Although the reported survival rate is about the GICC goal of 60%, further improvements in care are needed to increase survival to level closer to high-resource setting and decrease long term morbidity.